Analisis Tingkat Pemahaman Konsep Mahasiswa pada Mata Kuliah Statistik Melalui Metode Presentasi - Siregar, Rizka Fahruza; Purba, Oktaviana Nirmala; Saragih, Sri Rahma Dewi; Mapilindo, Mapilindo (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyse the level of students' understanding of concepts in Statistics courses and examine the impact of applying presentation methods in the learning process. The study uses a descriptive approach and was conducted in the Sharia Accounting class in Semester 3 at UINSU Medan in the 2024/2025 academic year. The research subjects were students in class AKS 3B, while the research object was a questionnaire designed to measure students' conceptual understanding of statistics material. The data obtained were analysed descriptively to describe the trends in students' conceptual understanding levels. The results showed that the average level of students' conceptual understanding ranged from 2.41 to 2.71. This range falls within the neutral category, i.e., between 2.1 and 3, indicating that students' conceptual understanding of statistical material through the presentation method is not yet fully optimal and still needs to be strengthened through more varied learning strategie